Optimizing raised bed dimensions for enhanced maize yield, water footprint reduction, and improved soil moisture dynamics under furrow irrigation (Asian Journal of Agriculture, 2024)
Abstract. Islam MT, Bhuyan MY, Das N, Jahan N, Rahman MM, Jewel MAH, Adham AKM. 2024. Optimizing raised bed dimensions for enhanced maize yield, water footprint reduction, and improved soil moisture dynamics under furrow irrigation. Asian J Agric 8: 10-22. Effective water management is crucial for sustainable agriculture, especially in regions facing water scarcity. This study examines the impact of different Raised Bed (RB) dimensions on maize (Zea mays L.) yield, Water Footprint (WF), and soil water content under furrow irrigation, with a focus on water conservation. The experiment, conducted at Bangladesh Agricultural University, Bangladesh, utilized a randomized complete block design featuring four irrigation treatments: the Conventional Method (CM) and three RB configurations with widths of 25 cm, 65 cm, and 110 cm. The RB65 treatment significantly improved maize yield, achieving 13.1±1.4 t/ha compared to 9.89±1.11 t/ha with CM. Additionally, RB65 peaked in water productivity, reducing irrigation water use by 37.72%, highlighting its potential for water conservation. Soil moisture retention was consistently higher across all RB treatments, with RB65 showing the greatest retention at depths up to 80 cm. It also recorded the lowest green WF (88.6±10.07 l/kg) and blue WF (12.63±1.43 l/kg), resulting in the lowest total WF (101.22±11.50 l/kg). These findings suggest that RB systems, particularly the 65 cm configuration, optimize water usage and enhance maize productivity, making it a viable strategy for resource management in water-limited areas. The study recommends adopting the RB65 configuration to maximize water efficiency and crop yields, contributing to food security and sustainable agricultural practices. However, these results are based on specific geographical and climatic conditions, limiting their generalizability to other regions or crops. Future research should explore long-term studies across diverse agro-ecological zones and examine various crops to validate the broader utility of the RB65 configuration.
Keywords: Maize yield, raised bed irrigation, soil water content, sustainable agriculture, water footprint, water management